Cholecystokinin-expressing neurons of the ventromedial hypothalamic nucleus control energy homeostasis - Eftychidis, Vasileios; Ellender, Tommas J.; Szymanski, Jacek; Minichiello, Liliana (Frontiers in Cellular Neuroscience, 2024)
The hypothalamus is the primary centre of the brain that regulates energy homeostasis. The ventromedial hypothalamus (VMH) plays a central role in maintaining energy balance by regulating food intake, energy expenditure, and glucose levels. However, the cellular and molecular mechanisms underlying its functions are still poorly understood. Cholecystokinin (CCK) is one of many genes expressed in this hypothalamic nucleus. Peripheral CCK regulates food intake, body weight, and glucose homeostasis. However, current research does not explain the function of CCK neurons in specific nuclei of the hypothalamus and their likely roles in network dynamics related to energy balance and food intake. This study uses genetic and pharmacological methods to examine the role of CCK-expressing neurons in the VMH (CCKVMH). Namely, using a previously generated BAC transgenic line expressing Cre recombinase under the CCK promoter, we performed targeted manipulations of CCKVMH neurons. Histological and transcriptomic database analysis revealed extensive distribution of these neurons in the VMH, with significant heterogeneity in gene expression related to energy balance, including co-expression with PACAP and somatostatin. Pharmacogenetic acute inhibition via Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) resulted in increased food intake and altered meal patterns, characterised by higher meal frequency and shorter intermeal intervals. Furthermore, diphtheria toxin-mediated ablation of CCKVMH neurons led to significant weight gain and hyperphagia over time, increasing meal size and duration. These mice also exhibited impaired glucose tolerance, indicative of disrupted glucose homeostasis. Our findings underscore the integral role of CCKVMH neurons in modulating feeding behaviour, energy homeostasis, and glucose regulation. This study enhances our understanding of the neurohormonal mechanisms underlying obesity and metabolic disorders, providing potential targets for therapeutic interventions.